The impact of social media use on suicide-related behavior - Arrazy, Muhammad Afdhal; Ndaru, Muhammad Tatag Adi; Sari, Nandha Mustika; Ariyanti, Mei Dwi; Ghosh, Anusua (Bulletin of Social Informatics Theory and Application, 2021)
Cyberbullying and addictive behavior are examples of the negative impacts that social media use that lead to suicidal thoughts. This study uses a systematic literature review to show the consequences of using social media that lead to suicidal behavior in various parts of the world. 37 articles were used to support this study that consists of 19 articles about cyberbullying and 18 articles about social media addiction. According to the findings of this report, there is a connection between cyberbullying and internet addiction and an increased risk of suicide or suicidal behavior among teenagers due to social media access. Addictive behavior of social media use has a direct effect on mental health and causes depression. Meanwhile, cyberbullying causes a lack of self-confidence, depression, frustration, self-awareness, and suicidal thoughts. Suicide is a way out for teenagers who experience various problems. Suicide prevention is also discussed.